Sodium ferric sulfate positive electrode material and preparation method and application thereof
The preparation of sodium iron sulfate positive electrode material by using carbon foam substrate and electrostatic spray deposition in sodium ion batteries, combining transition metal elements and antioxidants, solves the problem of poor material performance and achieves the improvement of high energy density and good cycle performance .
Patent Information
- Application Number
- CN202411371265.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-29
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2044-09-29
AI Technical Summary
The discharge specific capacity and rate performance of sodium ferric sulfate positive electrode material in sodium ion batteries is poor, mainly due to its large band gap and low intrinsic conductivity, resulting in limited carrier transfer and reaction kinetics, and the embedding and removal of sodium ions Irreversible, increasing internal impedance.
The carbon foam substrate and electrostatic spray deposition method are used to prepare sodium ferrosulfate positive electrode material, which increases the energy density and the transmission channel of sodium ions through the porous structure, and adds transition metal elements and antioxidants to form disordered structures to activate sodium storage sites and enhance Conductivity and cyclic stability.
It significantly improves the discharge specific capacity and conductivity of the sodium ferric sulfate positive electrode material, improves the rate performance and cycle stability, and extends the service life of the battery.
Smart Images

Figure BDA0005067646300000151
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of sodium ion batteries, and in particular to a sodium iron sulfate positive electrode material and a preparation method and application thereof. Background Art
[0002] Sodium iron sulfate cathode material has shown broad application prospects in the field of sodium ion batteries due to its advantages such as high specific capacity, good cycle stability, high temperature resistance, and low spontaneous combustion and explosion. This material usually has a high operating voltage (3.0-3.8V), is relatively abundant in resources, and has relatively low cost, so it has potential economic advantages in energy storage systems. However, although the theoretical energy density of sodium iron sulfate is high, in practical applications, due to its large band gap, low intrinsic conductivity, and limited rapid transfer and reaction kinetics of carriers (sodium ions and electrons), the battery has poor discharge capacity and rate performance. In addition, the bonding force between sodium and oxygen in the sodium iron sulfate material is strong, and sodium ions are not easy to break free, which leads to irreversible insertion and extraction of sodium ions, increases the migration resistance of sodium ions, leads to larger internal impedance, and reduces rate performance. Summary of the invention
[0003] Therefore, the technical problem to be solved by the present invention is to overcome the defects of the existing sodium iron phosphate positive electrode material in terms of poor discharge specific capacity and rate performance, thereby providing a sodium iron sulfate positive electrode material and a preparation method and application thereof that solve the above problems.
[0004] In order to achieve the above object, the present invention provides the following technical solutions:
[0005] A method for preparing a sodium iron sulfate positive electrode material, comprising:
[0006] obtaining a carbon foam substrate;
[0007] Weigh the raw materials according to the stoichiometric ratio of the sodium iron sulfate positive electrode material and add them into the solvent to obtain a mixed solution;
[0008] Depositing the mixed solution onto a carbon foam substrate by electrostatic spray deposition to obtain a precursor film;
[0009] The precursor film is sintered to obtain the sodium iron sulfate positive electrode material.
[0010] Preferably, the chemical formula of the sodium iron sulfate positive electrode material is Na x Fe y M z (SO4)3, 2.0≤x<3.0, 1.5<y≤2, 0≤z≤0.4, x+2y+2z=6, M is a transition metal element; among them, 0.05<z≤0.4 is preferred.
[0011] Preferably, the raw materials of the sodium iron sulfate positive electrode material include an iron source, a sodium source and a metal element additive;
[0012] And / or, an antioxidant or an antioxidant synergist is also added to the mixed solution.
[0013] Preferably, the iron source is ferrous sulfate heptahydrate;
[0014] And / or, the sodium source is anhydrous sodium sulfate;
[0015] And / or, the metal element additive is Ca 2+ Mg 2+ 、Al 3+ , Cu 2+ 、Zn 2+ ,La 3+ 、Ti 4+ , W 6+ At least one of which is a sulfate.
[0016] Preferably, the process of obtaining the mixed solution comprises: adding the raw materials into nitrogen-saturated water to fully dissolve them, and then mixing them with a mixed reagent consisting of an antioxidant, a synergist of the antioxidant, and an organic solvent to obtain a mixed solution.
[0017] Preferably, the water is ultrapure water;
[0018] And / or, the antioxidant is sodium acetate;
[0019] And / or, the antioxidant synergist is phosphoric acid;
[0020] And / or, the organic solvent is propylene glycol;
[0021] and / or, the mass of the raw material is 10-20% of the mass of water;
[0022] And / or, the mass of the water is 7-15% of the mass of the organic solvent;
[0023] Any / or, the weight of the antioxidant is 0.2-3% of the weight of the raw material;
[0024] And / or, the mass of the antioxidant synergist is 1.5-6% of the mass of the raw material.
[0025] Preferably, the sintering temperature is 750°C;
[0026] And / or, the sintering time is 8 hours;
[0027] And / or, the atmosphere of the sintering treatment is an inert atmosphere;
[0028] And / or, the sintering process is followed by pulverization, screening and demagnetization.
[0029] Preferably, the process of obtaining the carbon foam substrate comprises: heat-treating the melamine sponge under an inert atmosphere; preferably, the heat-treating temperature is 750-820° C., and the heat-treating time is 2-4 hours.
[0030] The present invention also provides a sodium ferric sulfate positive electrode material, which is prepared by the above-mentioned method for preparing the sodium ferric sulfate positive electrode material.
[0031] The present invention also provides application of the sodium iron sulfate positive electrode material in a sodium ion battery.
[0032] In the present invention, the transition metal element is the metal element additive.
[0033] The technical solution of the present invention has the following advantages:
[0034] 1. A method for preparing a sodium ferric sulfate positive electrode material, comprising: obtaining a carbon foam substrate; weighing raw materials according to the stoichiometric ratio of the sodium ferric sulfate positive electrode material and adding them to a solvent to obtain a mixed solution; depositing the mixed solution on the carbon foam substrate by electrostatic spray deposition to obtain a precursor film; sintering the precursor film to obtain the sodium ferric sulfate positive electrode material. The present invention uses carbon foam as a substrate material, and simultaneously performs electrostatic spray deposition to prepare a sodium ferric sulfate precursor, and then obtains the sodium ferric sulfate material by sintering. The porous structure of the foamed carbon provides a larger space for sodium ferric sulfate to accommodate active substances, which helps to improve the overall energy density of the positive electrode material. At the same time, the porous structure also provides a convenient channel for the rapid transmission of sodium ions, thereby improving the rate performance of the battery. Electrostatic spray deposition is a chemical deposition method that uses a high-voltage DC electrostatic field to disperse the charged aerosol under the dual effects of Coulomb repulsion and electrostatic attraction during the spraying process, and grows into a film on a high-temperature metal substrate. This method can achieve high-precision and uniform material deposition, thereby improving the electrochemical properties of the material. Moreover, the sodium iron sulfate material prepared by electrostatic spray deposition has a certain degree of disordered structure. This disordered structure can weaken the bonding force between sodium and oxygen, activate the sodium storage sites, and realize the reversible insertion and extraction of multiple sodium ions, which greatly improves the discharge capacity and conductivity of the material. At the same time, it can stabilize the structure and improve the cycle performance.
[0035] 2. In the preparation method of the sodium iron sulfate positive electrode material of the present invention, the carbon foam substrate is made of melamine sponge, which has the advantages of high open porosity, low density, high stability, environmental protection and multifunctionality. Specifically, the melamine sponge has a low density (e.g. 8.5 kg / m 3) and high stability, so that the positive electrode material can still maintain good cycle stability performance in high temperature environment. At the same time, the porosity of melamine sponge itself is as high as 99%, forming a three-dimensional grid structure, which enables it to provide extremely high specific surface area and pore volume when prepared into porous carbon materials; and this structure is not only conducive to the growth of materials such as carbon nanotubes, but also can enhance the mechanical strength and conductivity of the material. The above characteristics make the carbon foam substrate made of melamine sponge an ideal choice for the preparation of high-performance electrode materials (for example: positive electrode materials for supercapacitors).
[0036] 3. In the preparation method of the sodium iron sulfate positive electrode material of the present invention, the doping of transition metal elements can improve the conductivity of the positive electrode material, and at the same time stabilize the crystal structure of the positive electrode material, reduce the interface reaction between the material and the electrolyte and the loss of active substances, reduce the capacity loss rate of the battery during the cycle process, and further effectively extend the service life of the battery.
[0037] 4. In the preparation method of the sodium iron sulfate positive electrode material of the present invention, adding an antioxidant and an antioxidant synergist can prevent Fe 2+ Oxidized to Fe 3+ , reducing the impurity content in the material. DETAILED DESCRIPTION
[0038] The following examples are provided for a better understanding of the present invention, but are not intended to limit the best mode of implementation, nor to limit the content and protection scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior arts shall fall within the protection scope of the present invention.
[0039] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.
[0040] Example 1
[0041] This embodiment provides a method for preparing a sodium iron sulfate positive electrode material, and the specific steps are as follows:
[0042] 1) Cut the melamine sponge into pieces of 5×3.5×0.4cm 3 The thin block was placed in a tube furnace under argon atmosphere, and then heat treated at 820℃ for 3h to obtain elastic porous carbon foam, which was finally punched into discs with a diameter of 12mm.
[0043] 2) According to Na2Fe 1.6 Mg 0.4Weigh ferrous sulfate heptahydrate, anhydrous sodium sulfate, and magnesium sulfate in a stoichiometric ratio of (SO4)3, add the raw materials into ultrapure water saturated with nitrogen to fully dissolve to obtain an aqueous solution of metal salts, and then mix the aqueous solution of metal salts with a mixed reagent consisting of sodium acetate, phosphoric acid, and propylene glycol to obtain a mixed solution; wherein the total mass of ferrous sulfate heptahydrate, anhydrous sodium sulfate, and magnesium sulfate is 15% of the mass of ultrapure water, the mass of ultrapure water is 10% of the mass of propylene glycol, the mass of sodium acetate is 0.5% of the total mass of ferrous sulfate heptahydrate, anhydrous sodium sulfate, and magnesium sulfate, and the mass of phosphoric acid is 2% of the total mass of ferrous sulfate heptahydrate, anhydrous sodium sulfate, and magnesium sulfate. After continuous stirring for 5 hours, pour the solution into a 20 mL syringe with a syringe nozzle having a diameter of 1.2 mm;
[0044] 3) During the electrostatic spraying process, the distance between the carbon foam disc in step 1) and the nozzle was fixed at 2.8 cm. The disc temperature was set to 235° C. The voltage applied during the electrostatic spraying process was 7 kV to obtain a precursor film;
[0045] 4) placing the precursor film of step 3) into a tubular furnace, sintering the precursor film at 750° C. for 8 h in an argon atmosphere, cooling the film in the furnace, and finally crushing, sieving and demagnetizing the film to obtain a sodium iron sulfate positive electrode material.
[0046] Example 2
[0047] This embodiment provides a method for preparing a sodium iron sulfate positive electrode material, and the specific steps are as follows:
[0048] 1) Cut the melamine sponge into pieces of 5×3.5×0.4cm 3 The thin block was placed in a tube furnace under argon atmosphere, and then heat treated at 820℃ for 3h to obtain elastic porous carbon foam, which was finally punched into discs with a diameter of 12mm.
[0049] 2) According to Na2Fe 1.7 Mg 0.3 Weigh ferrous sulfate heptahydrate, anhydrous sodium sulfate, and magnesium sulfate in a stoichiometric ratio of (SO4)3, add the raw materials into ultrapure water saturated with nitrogen to fully dissolve to obtain an aqueous solution of metal salts, and then mix the aqueous solution of metal salts with a mixed reagent consisting of sodium acetate, phosphoric acid, and propylene glycol to obtain a mixed solution; wherein the total mass of ferrous sulfate heptahydrate, anhydrous sodium sulfate, and magnesium sulfate is 15% of the mass of ultrapure water, the mass of ultrapure water is 10% of the mass of propylene glycol, the mass of sodium acetate is 0.5% of the total mass of ferrous sulfate heptahydrate, anhydrous sodium sulfate, and magnesium sulfate, and the mass of phosphoric acid is 2% of the total mass of ferrous sulfate heptahydrate, anhydrous sodium sulfate, and magnesium sulfate. After continuous stirring for 5 hours, pour the solution into a 20 mL syringe with a syringe nozzle having a diameter of 1.2 mm;
[0050] 3) During the electrostatic spraying process, the distance between the carbon foam disc in step 1) and the nozzle was fixed at 2.8 cm. The disc temperature was set to 235° C. The voltage applied during the electrostatic spraying process was 7 kV to obtain a precursor film;
[0051] 4) placing the precursor film of step 3) into a tubular furnace, sintering the precursor film at 750° C. for 8 h in an argon atmosphere, cooling the film in the furnace, and finally crushing, sieving and demagnetizing the film to obtain a sodium iron sulfate positive electrode material.
[0052] Example 3
[0053] This embodiment provides a method for preparing a sodium iron sulfate positive electrode material, and the specific steps are as follows:
[0054] 1) Cut the melamine sponge into pieces of 5×3.5×0.4cm 3 The thin block was placed in a tube furnace under argon atmosphere, and then heat treated at 820℃ for 3h to obtain elastic porous carbon foam, which was finally punched into discs with a diameter of 12mm.
[0055] 2) According to Na2Fe 1.8 Mg 0.2 Weigh ferrous sulfate heptahydrate, anhydrous sodium sulfate, and magnesium sulfate in a stoichiometric ratio of (SO4)3, add the raw materials into ultrapure water saturated with nitrogen to fully dissolve to obtain an aqueous solution of metal salts, and then mix the aqueous solution of metal salts with a mixed reagent consisting of sodium acetate, phosphoric acid, and propylene glycol to obtain a mixed solution; wherein the total mass of ferrous sulfate heptahydrate, anhydrous sodium sulfate, and magnesium sulfate is 15% of the mass of ultrapure water, the mass of ultrapure water is 10% of the mass of propylene glycol, the mass of sodium acetate is 0.5% of the total mass of ferrous sulfate heptahydrate, anhydrous sodium sulfate, and magnesium sulfate, and the mass of phosphoric acid is 2% of the total mass of ferrous sulfate heptahydrate, anhydrous sodium sulfate, and magnesium sulfate. After continuous stirring for 5 hours, pour the solution into a 20 mL syringe with a syringe nozzle having a diameter of 1.2 mm;
[0056] 3) During the electrostatic spraying process, the distance between the carbon foam disc in step 1) and the nozzle was fixed at 2.8 cm. The disc temperature was set to 235° C. The voltage applied during the electrostatic spraying process was 7 kV to obtain a precursor film;
[0057] 4) placing the precursor film of step 3) into a tubular furnace, sintering the precursor film at 750° C. for 8 h in an argon atmosphere, cooling the film in the furnace, and finally crushing, sieving and demagnetizing the film to obtain a sodium iron sulfate positive electrode material.
[0058] Example 4
[0059] This embodiment provides a method for preparing a sodium iron sulfate positive electrode material, and the specific steps are as follows:
[0060] 1) Cut the melamine sponge into pieces of 5×3.5×0.4cm 3 The thin block was placed in a tube furnace under argon atmosphere, and then heat treated at 820℃ for 3h to obtain elastic porous carbon foam, which was finally punched into discs with a diameter of 12mm.
[0061] 2) According to Na2Fe 1.7 Zn 0.3 Weigh ferrous sulfate heptahydrate, anhydrous sodium sulfate, and magnesium sulfate in a stoichiometric ratio of (SO4)3, add the raw materials into ultrapure water saturated with nitrogen to fully dissolve to obtain an aqueous solution of metal salts, and then mix the aqueous solution of metal salts with a mixed reagent consisting of sodium acetate, phosphoric acid, and propylene glycol to obtain a mixed solution; wherein the total mass of ferrous sulfate heptahydrate, anhydrous sodium sulfate, and magnesium sulfate is 15% of the mass of ultrapure water, the mass of ultrapure water is 10% of the mass of propylene glycol, the mass of sodium acetate is 0.5% of the total mass of ferrous sulfate heptahydrate, anhydrous sodium sulfate, and magnesium sulfate, and the mass of phosphoric acid is 2% of the total mass of ferrous sulfate heptahydrate, anhydrous sodium sulfate, and magnesium sulfate. After continuous stirring for 5 hours, pour the solution into a 20 mL syringe with a syringe nozzle having a diameter of 1.2 mm;
[0062] 3) During the electrostatic spraying process, the distance between the carbon foam disc in step 1) and the nozzle was fixed at 2.8 cm. The disc temperature was set to 235° C. The voltage applied during the electrostatic spraying process was 7 kV to obtain a precursor film;
[0063] 4) placing the precursor film of step 3) into a tubular furnace, sintering the precursor film at 750° C. for 8 h in an argon atmosphere, cooling the film in the furnace, and finally crushing, sieving and demagnetizing the film to obtain a sodium iron sulfate positive electrode material.
[0064] Example 5
[0065] This embodiment provides a method for preparing a sodium iron sulfate positive electrode material, and the specific steps are as follows:
[0066] 1) Cut the melamine sponge into pieces of 5×3.5×0.4cm 3 The thin block was placed in a tube furnace under argon atmosphere, and then heat treated at 820℃ for 3h to obtain elastic porous carbon foam, which was finally punched into discs with a diameter of 12mm.
[0067] 2) Weigh ferrous sulfate heptahydrate, anhydrous sodium sulfate and magnesium sulfate according to the stoichiometric ratio of Na2Fe2(SO4)3, add the raw materials into ultrapure water saturated with nitrogen to fully dissolve to obtain an aqueous solution of metal salts, and then mix the aqueous solution of metal salts with a mixed reagent consisting of sodium acetate, phosphoric acid and propylene glycol to obtain a mixed solution; wherein the total mass of ferrous sulfate heptahydrate and anhydrous sodium sulfate is 15% of the mass of ultrapure water, the mass of ultrapure water is 10% of the mass of propylene glycol, the mass of sodium acetate is 0.5% of the total mass of ferrous sulfate heptahydrate and anhydrous sodium sulfate, and the mass of phosphoric acid is 2% of the total mass of ferrous sulfate heptahydrate and anhydrous sodium sulfate. After continuous stirring for 5 hours, pour the solution into a 20 mL syringe with a syringe nozzle having a diameter of 1.2 mm;
[0068] 3) During the electrostatic spraying process, the distance between the carbon foam disc in step 1) and the nozzle was fixed at 2.8 cm. The disc temperature was set to 235° C. The voltage applied during the electrostatic spraying process was 7 kV to obtain a precursor film;
[0069] 4) placing the precursor film of step 3) into a tubular furnace, sintering the precursor film at 750° C. for 8 h in an argon atmosphere, cooling the film in the furnace, and finally crushing, sieving and demagnetizing the film to obtain a sodium iron sulfate positive electrode material.
[0070] Example 6
[0071] This embodiment provides a method for preparing a sodium iron sulfate positive electrode material, and the specific steps are as follows:
[0072] 1) Cut the melamine sponge into pieces of 5×3.5×0.4cm 3 The thin block was placed in a tube furnace and an argon atmosphere was created. Then, the elastic porous carbon foam was obtained by heat treatment at 750°C for 4 h. Finally, the carbon foam was punched into a disc with a diameter of 12 mm.
[0073] 2) According to Na 2.6 Fe 1.6 Mg 0.1 Weigh ferrous sulfate heptahydrate, anhydrous sodium sulfate and magnesium sulfate in a stoichiometric ratio of (SO4)3, add the raw materials into ultrapure water saturated with nitrogen to fully dissolve to obtain an aqueous solution of metal salts, and then mix the aqueous solution of metal salts with a mixed reagent consisting of sodium acetate, phosphoric acid and propylene glycol to obtain a mixed solution; wherein the total mass of ferrous sulfate heptahydrate, anhydrous sodium sulfate and magnesium sulfate is 10% of the mass of ultrapure water, the mass of ultrapure water is 7% of the mass of propylene glycol, the mass of sodium acetate is 3% of the total mass of ferrous sulfate heptahydrate, anhydrous sodium sulfate and magnesium sulfate, and the mass of phosphoric acid is 6% of the total mass of ferrous sulfate heptahydrate, anhydrous sodium sulfate and magnesium sulfate. After continuous stirring for 5 hours, pour the solution into a 20mL syringe with a syringe nozzle having a diameter of 1.2mm;
[0074] 3) During the electrostatic spraying process, the distance between the carbon foam disc in step 1) and the nozzle was fixed at 2.8 cm. The disc temperature was set to 235° C. The voltage applied during the electrostatic spraying process was 7 kV to obtain a precursor film;
[0075] 4) placing the precursor film of step 3) into a tubular furnace, sintering the precursor film at 750° C. for 8 h in an argon atmosphere, cooling the film in the furnace, and finally crushing, sieving and demagnetizing the film to obtain a sodium iron sulfate positive electrode material.
[0076] Example 7
[0077] This embodiment provides a method for preparing a sodium iron sulfate positive electrode material, and the specific steps are as follows:
[0078] 1) Cut the melamine sponge into pieces of 5×3.5×0.4cm 3 The thin block was placed in a tube furnace and an argon atmosphere was created. Then, the elastic porous carbon foam was obtained by heat treatment at 820°C for 2 h. Finally, the carbon foam was punched into a disc with a diameter of 12 mm.
[0079] 2) According to Na2Fe 1.6 Mg 0.4 Weigh ferrous sulfate heptahydrate, anhydrous sodium sulfate, and magnesium sulfate in a stoichiometric ratio of (SO4)3, add the raw materials into ultrapure water saturated with nitrogen to fully dissolve to obtain an aqueous solution of metal salts, and then mix the aqueous solution of metal salts with a mixed reagent consisting of sodium acetate, phosphoric acid, and propylene glycol to obtain a mixed solution; wherein the total mass of ferrous sulfate heptahydrate, anhydrous sodium sulfate, and magnesium sulfate is 20% of the mass of ultrapure water, the mass of ultrapure water is 15% of the mass of propylene glycol, the mass of sodium acetate is 0.2% of the total mass of ferrous sulfate heptahydrate, anhydrous sodium sulfate, and magnesium sulfate, and the mass of phosphoric acid is 1.5% of the total mass of ferrous sulfate heptahydrate, anhydrous sodium sulfate, and magnesium sulfate. After continuous stirring for 5 hours, pour the solution into a 20 mL syringe with a syringe nozzle having a diameter of 1.2 mm;
[0080] 3) During the electrostatic spraying process, the distance between the carbon foam disc in step 1) and the nozzle was fixed at 2.8 cm. The disc temperature was set to 235° C. The voltage applied during the electrostatic spraying process was 7 kV to obtain a precursor film;
[0081] 4) placing the precursor film of step 3) into a tubular furnace, sintering the precursor film at 750° C. for 8 h in an argon atmosphere, cooling the film in the furnace, and finally crushing, sieving and demagnetizing the film to obtain a sodium iron sulfate positive electrode material.
[0082] Example 8
[0083] The difference between this embodiment and embodiment 2 is that only ultrapure water is used as the solvent and ferrous sulfate heptahydrate, anhydrous sodium sulfate, magnesium sulfate, sodium acetate and phosphoric acid are added to the solvent at the same time to obtain a mixed solution, and other conditions are the same as those in embodiment 2.
[0084] Example 9
[0085] The difference between this embodiment and embodiment 2 is that only propylene glycol is used as the solvent and ferrous sulfate heptahydrate, anhydrous sodium sulfate, magnesium sulfate, sodium acetate and phosphoric acid are added to the solvent at the same time to obtain a mixed solution, and other conditions are the same as those in embodiment 2.
[0086] Example 10
[0087] The difference between this embodiment and embodiment 2 is that ultrapure water and propylene glycol are first mixed as a mixed solvent, and then ferrous sulfate heptahydrate, anhydrous sodium sulfate, magnesium sulfate, sodium acetate, and phosphoric acid are simultaneously added to the mixed solvent to obtain a mixed solution, and other conditions are the same as those in embodiment 2.
[0088] Comparative Example 1
[0089] This comparative example provides a method for preparing a sodium iron sulfate positive electrode material, and the specific steps are as follows:
[0090] 1) According to Na2Fe 1.7 Mg 0.3 Weigh ferrous sulfate heptahydrate, anhydrous sodium sulfate and magnesium sulfate in a stoichiometric ratio of (SO4)3, add the raw materials into ultrapure water saturated with nitrogen to fully dissolve to obtain an aqueous solution of metal salts, and then evenly mix the aqueous solution of metal salts with sodium acetate, phosphoric acid and propylene glycol to obtain a mixed solution; wherein the total mass of ferrous sulfate heptahydrate, anhydrous sodium sulfate and magnesium sulfate is 15% of the mass of ultrapure water, the mass of ultrapure water is 10% of the mass of propylene glycol, the mass of sodium acetate is 0.5% of the total mass of ferrous sulfate heptahydrate, anhydrous sodium sulfate and magnesium sulfate, and the mass of phosphoric acid is 2% of the total mass of ferrous sulfate heptahydrate, anhydrous sodium sulfate and magnesium sulfate, and vigorously stir magnetically at 80°C overnight to form a black gel after the water in the solution evaporates;
[0091] 2) drying the gel obtained in step 1) in an oven at 120° C. overnight;
[0092] 3) placing the dried gel obtained in step 2) into a tubular furnace, sintering the dried gel at 750° C. for 8 h in an argon atmosphere, cooling the gel in the furnace, and finally crushing, sieving and demagnetizing the gel to obtain a sodium iron sulfate positive electrode material.
[0093] Comparative Example 2
[0094] This comparative example provides a method for preparing a sodium iron sulfate positive electrode material, and the specific steps are as follows:
[0095] 1) Melamine is dissolved in a methanol solvent to form a melamine solution, wherein the mass of melamine is 15% of the mass of methanol, and then the melamine solution is evenly applied on a fiber net and dried in an argon atmosphere to form a solid melamine film. The melamine film is heated to a high temperature (800°C) in an argon atmosphere for 6 hours to cause pyrolysis and carbonization of melamine to convert it into a carbon-rich structure, and finally, after cooling, washing and drying, melamine carbon paper is obtained;
[0096] 2) Weigh ferrous sulfate heptahydrate, anhydrous sodium sulfate and magnesium sulfate according to the stoichiometric ratio of Na2Fe2(SO4)3, add the raw materials into nitrogen-saturated ultrapure water to fully dissolve to obtain an aqueous solution of metal salts, and then mix the aqueous solution of metal salts with sodium acetate, phosphoric acid and propylene glycol to obtain a mixed solution; wherein the total mass of ferrous sulfate heptahydrate and anhydrous sodium sulfate is 15% of the mass of ultrapure water, the mass of ultrapure water is 10% of the mass of propylene glycol, the mass of sodium acetate is 0.5% of the total mass of ferrous sulfate heptahydrate and anhydrous sodium sulfate, and the mass of phosphoric acid is 2% of the total mass of ferrous sulfate heptahydrate and anhydrous sodium sulfate. After continuous stirring for 5 hours, pour the solution into a 20 mL syringe with a syringe nozzle having a diameter of 1.2 mm;
[0097] 3) During the electrostatic spraying process, the distance between the carbon paper substrate in step 1) and the nozzle was fixed at 2.8 cm, the temperature of the carbon paper substrate was set to 235° C., and the voltage applied during the electrostatic spraying process was 7 kV to obtain a precursor film;
[0098] 4) placing the precursor film of step 3) into a tubular furnace, sintering the precursor film at 750° C. for 8 h in an argon atmosphere, cooling the film in the furnace, and finally crushing, sieving and demagnetizing the film to obtain a sodium iron sulfate positive electrode material.
[0099] Comparative Example 3
[0100] This comparative example provides a method for preparing a sodium iron sulfate positive electrode material, and the specific steps are as follows:
[0101] 1) Melamine is dissolved in a methanol solvent to form a melamine solution, wherein the mass of melamine is 15% of the mass of methanol, and then the melamine solution is evenly applied on a fiber net and dried in an argon atmosphere to form a solid melamine film. The melamine film is heated to a high temperature (800°C) in an argon atmosphere for 6 hours to cause pyrolysis and carbonization of melamine to convert it into a carbon-rich structure, and finally, after cooling, washing and drying, melamine carbon paper is obtained;
[0102] 2) According to Na2Fe 1.7 Mg 0.3Weigh ferrous sulfate heptahydrate, anhydrous sodium sulfate and magnesium sulfate in a stoichiometric ratio of (SO4)3, add the raw materials into ultrapure water saturated with nitrogen to fully dissolve to obtain an aqueous solution of metal salts, and then mix the aqueous solution of metal salts with sodium acetate, phosphoric acid and propylene glycol to obtain a mixed solution; wherein the total mass of ferrous sulfate heptahydrate and anhydrous sodium sulfate is 15% of the mass of ultrapure water, the mass of ultrapure water is 10% of the mass of propylene glycol, the mass of sodium acetate is 0.5% of the total mass of ferrous sulfate heptahydrate and anhydrous sodium sulfate, and the mass of phosphoric acid is 2% of the total mass of ferrous sulfate heptahydrate and anhydrous sodium sulfate. After continuous stirring for 5 hours, pour the solution into a 20mL syringe with a syringe nozzle having a diameter of 1.2mm;
[0103] 3) During the electrostatic spraying process, the distance between the carbon paper substrate in step 1) and the nozzle was fixed at 2.8 cm, the temperature of the carbon paper substrate was set to 235° C., and the voltage applied during the electrostatic spraying process was 7 kV to obtain a precursor film;
[0104] 4) placing the precursor film of step 3) into a tubular furnace, sintering the precursor film at 750° C. for 8 h in an argon atmosphere, cooling the film in the furnace, and finally crushing, sieving and demagnetizing the film to obtain a sodium iron sulfate positive electrode material.
[0105] Test Example 1
[0106] The electrical performance test of the sodium iron sulfate positive electrode material prepared in the embodiment and the comparative example is carried out. The electrical performance test conditions are as follows: the electrode is made by homogenizing and coating at a ratio of 95 (main material): 2.5 (PVDF): 2.5 (SP), metallic sodium is used as the counter electrode, glass fiber is used as the diaphragm, and 1 mol / L NaPF6 ethylene carbonate (EC) / dimethyl carbonate (DMC) (volume ratio 1:1) solution is used as the electrolyte. The positive electrode, sodium sheet, diaphragm, gasket and spring are placed in a button cell to assemble a CR2032 button cell. Finally, the button cell is placed in a blue electric test system for electrical performance testing. The electrical performance test parameters were set as follows: voltage range 2.0V-4.5V, capacity test at 0.1C / 0.1C charge and discharge in the first cycle, and then rate performance was evaluated at 0.2C / 0.2C, 0.5C / 0.5C, and 1C / 1C charge and discharge tests, and finally cycle performance was evaluated at 1C / 1C for 50 cycles. The test results are shown in Table 1.
[0107] Table 1
[0108]
[0109] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the invention.
Claims
1. A method for preparing a sodium iron sulfate positive electrode material, characterized in that: include: obtaining a carbon foam substrate; Weigh the raw materials according to the stoichiometric ratio of the sodium iron sulfate positive electrode material and add them into the solvent to obtain a mixed solution; Depositing the mixed solution onto a carbon foam substrate by electrostatic spray deposition to obtain a precursor film; The precursor film is sintered to obtain the sodium iron sulfate positive electrode material.
2. The preparation method according to claim 1, characterized in that: The chemical formula of the sodium iron sulfate positive electrode material is Na x Fe y M z (SO4)3, 2.0≤x<3.0, 1.5<y≤2, 0≤z≤0.4, x+2y+2z=6, M is a transition metal element; among them, 0.05<z≤0.4 is preferred.
3. The preparation method according to claim 2, characterized in that: The raw materials of the sodium iron sulfate positive electrode material include an iron source, a sodium source and a metal element additive; And / or, an antioxidant or an antioxidant synergist is also added to the mixed solution.
4. The preparation method according to claim 3, characterized in that: The iron source is ferrous sulfate heptahydrate; And / or, the sodium source is anhydrous sodium sulfate; And / or, the metal element additive is Ca 2+ Mg 2+ 、Al 3+ , Cu 2+ 、Zn 2+ ,La 3+ 、Ti 4+ , W 6+ At least one of which is a sulfate.
5. The preparation method according to claim 3 or 4, characterized in that: The process of obtaining the mixed solution includes: adding the raw materials into nitrogen-saturated water to fully dissolve them, and then mixing them with a mixed reagent consisting of an antioxidant, a synergist of the antioxidant, and an organic solvent to obtain a mixed solution.
6. The preparation method according to claim 5, characterized in that: The water is ultrapure water; And / or, the antioxidant is sodium acetate; And / or, the antioxidant synergist is phosphoric acid; And / or, the organic solvent is propylene glycol; and / or, the mass of the raw material is 10-20% of the mass of water; And / or, the mass of the water is 7-15% of the mass of the organic solvent; Any / or, the weight of the antioxidant is 0.2-3% of the weight of the raw material; And / or, the mass of the antioxidant synergist is 1.5-6% of the mass of the raw material.
7. The preparation method according to any one of claims 1 to 6, characterized in that: The sintering temperature is 750°C; And / or, the sintering time is 8 hours; And / or, the atmosphere of the sintering treatment is an inert atmosphere; And / or, the sintering process is followed by pulverization, screening and demagnetization.
8. The preparation method according to any one of claims 1 to 7, characterized in that: The process of obtaining the carbon foam substrate comprises: heat-treating the melamine sponge in an inert atmosphere; preferably, the heat-treating temperature is 750-820° C., and the heat-treating time is 2-4 hours.
9. A sodium iron sulfate positive electrode material, characterized in that: The cathode material is prepared by the method for preparing the sodium iron sulfate cathode material according to any one of claims 1 to 8.
10. Use of the sodium iron sulfate positive electrode material according to claim 9 in sodium ion batteries.
Citation Information
Patent Citations
Composite sodium ferrous sulfate positive electrode material as well as preparation method and application thereof
CN116995227A
Carbon-coated sodium ferric sulfate positive electrode material as well as preparation method and application thereof
CN117334863A
Sodium ferric sulfate positive electrode material and preparation method and application thereof
CN117800400A
Cited By
High-performance sodium ferric sulfate polyanion positive electrode material and preparation method thereof
CN119864415A
High-capacity Na2Fe2 (SO4) 3 (at) Na3Fe2 (SO4) 3F (at) CNT positive electrode material and preparation method and application thereof
CN121426178A
A high-capacity Na2Fe2(SO4)3@Na3Fe2(SO4)3F@CNT cathode material, its preparation method, and its application.
CN121426178B
Doped sodium ferric sulfate positive electrode material as well as preparation method and application thereof
CN121687947A